Single-nucleus RNA-seq2 reveals functional crosstalk between liver zonation and ploidy - M. L. Richter (Nature Portfolio, 2021)
Single-cell RNA-seq reveals the cellular heterogeneity in development and disease. Here the authors present a single-nucleus RNA-seq2 that allows deep characterization of nuclei isolated from frozen archived tissues, apply it for transcriptional profiling of individual hepatocytes, and determine a functional crosstalk between liver zonation and ploidy.